Assessing the association between tourism and the alcohol urban environment in Barcelona: a cross-sectional study - Xisca Sureda; Manuel Franco; Susanna Puigcorbé; Joan R Villalbí; Marina Bosque-Prous; Ester Teixidó-Compañó; Montserrat Bartroli; Albert Espelt (BMJ Open)
Objectives Alcohol availability and promotion are not distributed equally in the urban context. Evidence shows that the socioeconomic level seems to influence the amount of alcohol-related elements in an area. Some studies suggest that tourism could also affect the distribution of these elements. We explore with a valid instrument in a large city whether there is an association between high tourism pressure and a greater presence of alcohol-related elements in the urban environment.Design Observational ecological study.Setting The study was conducted in Barcelona during 2017–2018.Participants We assessed urban exposure to alcohol by performing social systematic observation using the OHCITIES Instrument in a stratified random sample of 170 census tracts within the city’s 73 neighbourhoods.Primary and secondary outcome measures For each census tract we calculated the density of alcohol premises, and of promotion in public places per 1000 residents. We estimated tourism pressure using the number of tourist beds per 1000 residents in each neighbourhood and calculated quartiles. To assess the relationship between rate ratios of elements of alcohol urban environment and tourism pressure, we calculated Spearman correlations and fitted Poisson regression models with robust error variance.Results The median densities obtained were of 8.18 alcohol premises and of 7.59 alcohol advertising and promotion elements visible from the public space per 1000 population. Census tracts with the highest tourism pressure had 2.5 (95% CI: 1.85–3.38) times more outlets and 2.3 (95% CI: 1.64–3.23) times more promotion elements per 1000 residents than those in the lowest tourism pressure quartile.Conclusions We observed a strong association between tourism pressure and alcohol exposure in the city of Barcelona.